2014
DOI: 10.1080/01694243.2014.925387
|View full text |Cite
|
Sign up to set email alerts
|

A detailed experimental study of the effects of pre-bond contamination with a hydraulic fluid, thermal degradation, and poor curing on fracture toughness of composite-bonded joints

Abstract: Adhesive bonding is applied by the aircraft industry both for assembling composite structural parts and implementing composite patch repairs in damaged structural parts. In both applications, there exist several scenarios, related to surface contamination and processing, that could affect bonding quality and thus, degrade bond strength. In this paper, the detailed effects of pre-bond contamination with a hydraulic fluid, thermal degradation of the composite substrate, as well as poor curing (lower curing tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 21 publications
0
24
0
1
Order By: Relevance
“…[3,4,5] As a consequence, fracture toughness values under opening mode (G IC ) significantly decrease, which is a direct result from the crack growing at the interface instead of inside the adhesive layer (cohesive failure-good adhesion quality). [6,7] The same studies also show that neither ultrasonic C-scan nor X-ray tomography are able to detect those defects prior to testing.…”
Section: Introductionmentioning
confidence: 80%
“…[3,4,5] As a consequence, fracture toughness values under opening mode (G IC ) significantly decrease, which is a direct result from the crack growing at the interface instead of inside the adhesive layer (cohesive failure-good adhesion quality). [6,7] The same studies also show that neither ultrasonic C-scan nor X-ray tomography are able to detect those defects prior to testing.…”
Section: Introductionmentioning
confidence: 80%
“…According to the literature, the pre-bond thermal treatment results in decrease of GIC value by 10 and 13 % for treatment at 190 and 200°C, respectively [1]. In the case of treatment at 210°C the increase by 9% was observed [1]. In the case of improper curing of the adhesive, it was shown that the lowered temperature have great impact on the bond performance.…”
Section: Introductionmentioning
confidence: 99%
“…The pre-bond contamination or modification have an influence on the fracture toughness of the CFRP bonded joints. According to the literature, the pre-bond thermal treatment results in decrease of GIC value by 10 and 13 % for treatment at 190 and 200°C, respectively [1]. In the case of treatment at 210°C the increase by 9% was observed [1].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is evidence of adhesion strength improvement for the case of the low temperature. Thermal degradation results in the thermo-oxidation of the resin [16,24]. Depending on the temperature level applied, this may either lead to the improvement of the resin performance due to the presence of carboxyl bonds or cause the development of an oxidized layer which hinders the adhesion at the surface of the CFRP substrate [16].…”
Section: Hoffmann Et Almentioning
confidence: 99%
“…the fuselage parts stroked by lightning [24] causing local overheating and damage of the matrix or the wing parts which are close to the engines. Besides the loss in the mechanical properties of the structural parts, thermal degradation of the CFRP parts might also affect bonding in a repair.…”
Section: Pre-bond Contamination Of Cfrpsmentioning
confidence: 99%